Ruguo renquan qinfan wushiwudi bu zai fasheng, zhu renquan zenmo hui shi ni wuguande chouxiang shiwu?
'When human rights violations no longer happen anywhere anytime, how can all human rights then be abstract things which have nothing to do with you?'